2014
DOI: 10.1088/1367-2630/16/11/113046
|View full text |Cite
|
Sign up to set email alerts
|

Multicellular automaticity of cardiac cell monolayers: effects of density and spatial distribution of pacemaker cells

Abstract: The biological pacemaker approach is an alternative to cardiac electronic pacemakers. Its main objective is to create pacemaking activity from added or modified distribution of spontaneous cells in the myocardium. This paper aims to assess how automaticity strength of pacemaker cells (i.e. their ability to maintain robust spontaneous activity with fast rate and to drive neighboring quiescent cells) and structural linear anisotropy, combined with density and spatial distribution of pacemaker cells, may affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“… and N cluster as a function of D aut and displayed remarkable similarities with our previous study [ 14 ], despite different model structure and different number of neighbors. In fact, average of the maximum PM cluster size monotonically increased with D aut , with a transition around D aut = 0.5 ( Fig 5 ).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“… and N cluster as a function of D aut and displayed remarkable similarities with our previous study [ 14 ], despite different model structure and different number of neighbors. In fact, average of the maximum PM cluster size monotonically increased with D aut , with a transition around D aut = 0.5 ( Fig 5 ).…”
Section: Discussionsupporting
confidence: 85%
“…Our previous study [ 14 ] demonstrated that not only the density but also the spatial distribution of PM cells may induce important intrinsic variability in the BP dynamical behavior. The study focused on a simple continuous and isotropic 2D substrate with a single period of activity for the autonomous cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, spontaneous activity in cultured cells starts at one specific point on the periphery of the cell monolayer and propagates through gap junctions like a 2-dimensional wave (Supplementary Fig. 1) [48,49]. Conversely, field stimulation induces an almost instantaneous excitation across the cell monolayer and, consequently, pulse propagation does not occur.…”
Section: Discussionmentioning
confidence: 99%